Pelatihan Analisis Bibliometrik Berbasis Vosviewer dan Publish or Perish Bagi Dosen Kopertip Indonesia - Dadang Sudrajat; Bani Nurhakim; Suteja; Syaiful Imanudin (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Strengthening the research capacity of university lecturers is a crucial aspect of improving the quality of higher education in Indonesia. One relevant skill to support research development and scientific publication is the ability to conduct bibliometric analysis. This analysis is useful for mapping research trends, identifying scientific collaborations, and determining potential research topics through the study of references and citations. This Community Service Program (PKM) aims to provide training in bibliometric analysis using the software tools VOSviewer and Publish or Perish for lecturers affiliated with Kopertip Indonesia (Coordinator of Indonesian Private Universities). The training was conducted both online and offline, using a combination of theoretical and practical approaches. The materials covered included basic bibliometric concepts, methods for accessing scholarly publication data (e.g., from Google Scholar and Scopus), and hands on practice using Publish or Perish to extract bibliometric data and VOSviewer to visualize the analysis results in the form of term maps and author collaboration networks. The training was also complemented by case studies from various fields of science. Evaluation results indicated that the training improved participants’ understanding and skills in using both tools. Participating lecturers reported increased confidence in mapping research topics, selecting relevant journals, and planning more targeted publication strategies. This activity not only enhanced digital research competencies but also encouraged lecturers to be more productive in contributing to national and international scientific outputs. In the future, this type of training can be replicated across other higher education environments as part of efforts to strengthen a data-driven academic ecosystem.